MoSi2/Al2O3/Feldspar Composites for Injection‐Molded Ceramic Heating Elements. Issue 9 (16th August 2021) - Wick-Joliat, René; Mauchle, Stéphane; Kontic, Roman; Ehrat, Sandro; Hocker, Thomas; Penner, Dirk
Abstract : MoSi2 is an electrically conductive material with numerous applications mostly in high‐temperature environments. Herein, the production of MoSi2 ‐containing resistive heating elements by ceramic injection molding (CIM) is described. The sintered parts consist of MoSi2 particles embedded in a matrix of vitrified feldspar and Al2 O3 . The conductivity of sintered parts can be tuned precisely by varying the content of the conductive phase. For the development of the injection‐molding feedstock, four binder systems are evaluated. The corresponding feedstocks are injection molded into different geometries in traditional molds as well as in additively manufactured, soluble molds. For each feedstock, a debinding and sintering routine is elaborated based on thermogravimetric measurements. Higher debinding temperature leads to more oxidation of MoSi2 and less conductive samples. Therefore, the conductivity as well as density of sintered parts is used to evaluate the applicability of the feedstocks. Finally, glow tests prove that MoSi2 /Al2 O3 /feldspar composite parts can be used as heating elements and by combining infrared temperature measurement data with computational simulations important material data such as thermal and electrical conductivity and thermal capacity can be obtained reliably. Abstract : Herein, the fabrication of heating elements from a MoSi2 /Al2 O3 /feldspar composite is presented. MoSi2 is chosen for its conductivity, Al2 O3 allows the tailoring of the conductivity and feldspar creates a protective vitreous coating around MoSi2 particles to avoid oxidation at high temperatures. Different binder systems are investigated and heating elements are produced by ceramic injection molding for high throughput and precision.